A Study to Assess the Attitude and Acceptance toward COVID-19 Vaccine among General Public - Bijitha Biju; M. Melvin David; J. Balalakshmi (Archives of Medicine and Health Sciences)
Background and Aim: COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. While most people experience mild-to-moderate respiratory illness and recover without special treatment, some, especially older people and those with underlying medical conditions, may become seriously ill. To prevent transmission, it is important to be informed about the disease and how it spreads. This includes staying at least 1 m apart from others, wearing a properly fitted mask, washing your hands frequently, getting vaccinated, and following local guidance. The virus spreads through small liquid particles from an infected person’s mouth or nose when they cough, sneeze, speak, sing, or breathe. Practicing respiratory etiquette and self-isolating when feeling unwell are important measures to take. SARS-CoV-1 and SARS-CoV-2 are genetically similar viruses responsible for global epidemics of different scales. They diverged due to differences in transmission dynamics and clinical presentations. COVID-19 management has evolved with new knowledge, therapeutics, and vaccines. The impact on health care and public health systems has been profound, with lessons learned for future pandemics. A globally fair vaccine distribution system must prevail over vaccine nationalism for the world to return to its prepandemic status. Materials and Methods: A quantitative cross-sectional study conducted in a tertiary care hospital among 272 participants who were selected conveniently. The attitude was assessed using self-structured five-point Likert scale, and acceptance was assessed using self-structured dichotomous questionnaire. Results: About 64.0% of the general public had good attitude, 31.3% of the general public had moderate attitude, and 4.8% of the general public had excellent attitude, none of them had poor attitude. The majority 95.6% of the general public expressed acceptance toward the COVID-19 vaccine and 4.4% of them not. Correlation of attitude and acceptance toward COVID-19 the r = 0.15 was significant at the level of P < 0.01. The association between attitude and demographic variables of the public revealed such as occupation, family monthly income, and any of the family members vaccinated had significant association at the level of P <0.01. Association between acceptance and demographic variables of the public revealed such as, age, vaccinated participants, and any of the family members vaccinated had significant association with acceptance at the level of P < 0.01. Conclusion: This study provides valuable insights into the attitude and acceptance toward COVID-19 vaccine among general public. These findings can help to inform strategies for increasing vaccination rates and ultimately protecting public health.